CONFLICT MANAGEMENT IN MUSLIM FAMILIES AS A MEANS OF PREVENTING DIVORCE FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Ike Yulisa; Rachel Chan (Sharia Oikonomia Law Journal, 2026)
The rising divorce rate among Muslim families indicates that domestic conflicts have not been effectively managed in accordance with the principles of Islamic family law. Conflicts stemming from economic factors, communication, gender roles, and differences in religious values often escalate into prolonged disputes that lead to divorce, even though Islam regards divorce as a last resort. This study aims to analyze the concepts and practices of conflict management in Muslim families from the perspective of Islamic family law as a preventive measure against divorce. The study employs a library research method with a descriptive qualitative approach. Data is sourced from classical and contemporary fiqh literature, academic journals, scholarly works, and Islamic family law regulations. Analysis is conducted using content analysis techniques to systematically examine the relationship between the normative principles of Islamic family law and strategies for managing family conflicts. Research findings indicate that Islamic family law possesses a comprehensive normative framework for conflict resolution, encompassing the principles of ishlah (reconciliation), musyawarah (deliberation), and justice ('adl), as well as the mechanisms of nasihat (counseling) and tahkim (family arbitration). This framework has the substantive potential to serve as a preventive tool against divorce. However, its full realization is hindered by a lack of understanding and implementation in the daily lives of Muslim families. The gap between ideal norms and actual practices is the root of the problem that must be addressed through educational and institutional approaches. This study confirms that conflict management based on Islamic family law plays a strategic role in reducing divorce rates and strengthening the resilience of Muslim families. These findings are expected to contribute to the development of Islamic family law that is more responsive to the dynamics of contemporary family conflicts.